Coordinated Optimal Short-Term Operation of Hydro-Wind-Solar Integrated Systems. (February 2019) - Zhang, Hongxuan; Hu, Wei; Yu, Rui; Tang, Maolin
Abstract: The integration of high proportion variable renewable energy sources (RES) has greatly threatened the safe and stable operation of power systems. Considering the complementary characteristics of various RES, this paper proposes a short-term optimization model for cascade hydropower stations coupled with renewable-based generations including wind and photovoltaic (PV). Based on autoregressive moving average (ARMA) model and copula function, a joint distribution model for power output of wind and PV is built with measured data and substantial scenarios are produced. Due to the nonlinear curve of forebay elevation - reservoir volume and tailwater elevation - water flow in hydropower stations, several linearization approaches are used to reformulate the optimization model into a tractable form. Hydraulic relationship and time delay of water flow between cascade reservoirs are established to make full use of the controllable complementarity of hydropower generations, and the variability of wind and PV power output can be mitigated. A basin in southwest China with wind farms and solar arrays is chosen as a detailed study case. The simulation results demonstrate the applicability and effectiveness of the proposed approach.